Pengelolaan Objek Wisata Danau Paisupok Dalam Meningkatkan Pendapatan Asli Desa (PAD-Des) Di Desa Lukpanenteng Kecamatan Bulagi Utara Kabupaten Banggai Kepulauan - Bete, Siti Fadila; Alhadar, Sofyan; Bakari, Luthfia (Universitas Pahlawan Tuanku Tambusai, 2024)
Banggai Islands Regency, which is located in Central Sulawesi Province, has great tourism potential. This area offers extraordinary natural beauty such as exotic beaches, mountains and enchanting lakes. One of the interesting natural tourist destinations in this district is Lake Paisupok which is located in Lukpanenteng Village, North Bulagi District, Banggai Islands Regency. Lake Paisupok has great potential for development as a tourist attraction. However, the management and use of this lake is still limited because tourism management requires complex efforts and involves all related parties. The aim of this research is to find out how the Paisupok Lake tourist attraction is managed in Lukpanenteng village, North Bulagi sub-district, Banggai Islands district. This research uses a qualitative research method with a descriptive approach, which aims to understand social and cultural phenomena from the perspective of the participants or subjects studied, so that they can describe existing problems. This research focuses on the management of the Lake Paisupok tourist attraction located in Lukpanenteng Village, North Bulagi District, Banggai Islands Regency, The results of this research show; First, from an implementation perspective, the management of the Lake Paisupok tourist attraction is still not optimal or less effective. Second, in terms of organization, its effectiveness is still not fully optimal. Third, from an implementation perspective, the management of the Lake Paisupok tourist attraction still relies heavily on the deliberation process in decision making. Even though deliberation is a democratic approach, its implementation is often not optimal because the decision-making process takes a long time. Keywords: Management, tourist attractions, Paisupok Lake